2020
DOI: 10.1101/2020.04.05.20049346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N95 Mask Decontamination using Standard Hospital Sterilization Technologies

Abstract: The response to the COVID19 epidemic is generating severe shortages of personal protective equipment around the world. In particular, the supply of N95 respirator masks has become severely depleted with supplies having to be rationed and health care workers having to use masks for prolonged periods in many countries. We sought to test the ability of 4 different decontamination methods including autoclave treatment, ethylene oxide gassing, ionized hydrogen peroxide fogging and vaporized hydrogen peroxide exposu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
206
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(214 citation statements)
references
References 11 publications
3
206
0
5
Order By: Relevance
“…While Bioquell is approved under an FDA EUA for 20 cycles, N95 masks sterilized using an alternative HPGP method commercialized by Sterrad fail at five cycles (the Sterrad EUA was approved for 2 sterilization cycles and requires that a mask be returned to a single user). 8,29 Moreover, our data show that semi-enclosed items of PPE, such as PAPR hoses, cannot be sterilized without pre-treatment, and that face shields with thick foam may not be sterile even after iHP pre-treatment followed by iHP treatment in an environmental chamber. Thus, it is imperative that institutions seeking to deploy iHP/VHP technology review available primary data prior to local deployment.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…While Bioquell is approved under an FDA EUA for 20 cycles, N95 masks sterilized using an alternative HPGP method commercialized by Sterrad fail at five cycles (the Sterrad EUA was approved for 2 sterilization cycles and requires that a mask be returned to a single user). 8,29 Moreover, our data show that semi-enclosed items of PPE, such as PAPR hoses, cannot be sterilized without pre-treatment, and that face shields with thick foam may not be sterile even after iHP pre-treatment followed by iHP treatment in an environmental chamber. Thus, it is imperative that institutions seeking to deploy iHP/VHP technology review available primary data prior to local deployment.…”
Section: Resultsmentioning
confidence: 93%
“…The possibility that disposable N95 masks could be sterilized and reused was raised 15 years ago as a strategy to address shortages arising from medical emergencies, [3][4][5] but with the exception of a single FDA-funded study by the Battelle Memorial Institute, 6 little subsequent research was performed on the topic. Recently, in response to acute N95 mask shortages, multiple strategies for mask sterilization have been proposed and studied, including exposure to ultraviolet (UV) germicidal irradiation, vaporized hydrogen peroxide, moist heat, ethylene oxide, and gamma irradiation [7][8][9][10][11][12][13][14] . In this study, we evaluate a recently developed technology, ionized hydrogen peroxide (iHP), as a method for sterilizing N95 masks and other PPE.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kumar et al reported no recoverable SARS-CoV-2 viruses on N95 FFR surfaces after the masks undergo a one-hour treatment cycle involving 10 minutes of dehumidification, 3 minutes of conditioning, 30 minutes of decontamination, and 20 minutes of aeration. Throughout the process, the peak HPV concentration of 750 ppm and the FFRs can undergo 10 cycles of treatment without compromise to mask performance [115]. Likewise, Smith et al also reported no functional degradation to N95 FFRs (both filtering capacity and fit factor) after two cycles of VHP treatments involving 20 minutes of gassing (~500 ppm), 60 minutes of dwelling (~420 ppm), and 210 minutes of aeration at ambient temperature, with no viable virus detected at the end of each cycle [116].…”
Section: Decontamination By Hydrogen Peroxidementioning
confidence: 99%
“…We previously reported that a high-level disinfection cabinet that generates aerosolized peracetic acid (PAA) (also known as peroxyacetic acid) and hydrogen peroxide was effective for disinfection of N95 respirators. 18,19 Here, we expanded on these promising findings by evaluating the use of the technology on a larger scale.…”
Section: Introductionmentioning
confidence: 99%